Post‐transcriptional adaptation of the aquatic plant Spirodela polyrhiza under stress and hormonal stimuli. (6th April 2019) - Fourounjian, Paul; Tang, Jie; Tanyolac, Bahattin; Feng, Yaping; Gelfand, Brian; Kakrana, Atul; Tu, Min; Wakim, Chris; Meyers, Blake C.; Ma, Jiong; Messing, Joachim
Summary: The Lemnaceae family comprises aquatic plants of angiosperms gaining attention due to their utility in wastewater treatment, and rapid production of biomass that can be used as feed, fuel, or food. Moreover, it can serve as a model species for neotenous growth and environmental adaptation. The latter properties are subject to post‐transcriptional regulation of gene expression, meriting investigation of how miRNAs in Spirodela polyrhiza, the most basal and most thoroughly sequenced member of the family, are expressed under different growth conditions. To further scientific understanding of its capacity to adapt to environmental cues, we measured miRNA expression and processing of their target sequences under different temperatures, and in the presence of abscisic acid, copper, kinetin, nitrate, and sucrose. Using two small RNA sequencing experiments and one degradome sequencing experiment, we provide evidence for 108 miRNAs. Sequencing cleaved mRNAs validated 42 conserved miRNAs with 83 targets and 24 novel miRNAs regulating 66 targets and created a list of 575 predicted and verified targets. These analyses revealed condition‐induced changes in miRNA expression and cleavage activity, and resulted in the addition of stringently reviewed miRNAs to miRBase. This combination of small RNA and degradome sequencing provided not only high confidence predictions of conserved and novel miRNAs and targets, but also a view of the post‐transcriptional regulation of adaptations. A unique aspect is the role of miR156 and miR172 expression and activity in its clonal propagation and neoteny. Additionally, low levels of 24 nt sRNAs were observed, despite the lack of recent retrotransposition. Significance Statement: Taking advantage of the sequenced genome of an aquatic species, the expression of miRNA and processing of its targets sites in response to environmental adaptation was investigated, providing an enhanced miRNA database.